Characteristics Analysis and Testing of SMA Spring Actuator - Jianzuo Ma; Haolei Huang; Jin Huang (Advances in Materials Science and Engineering)
The biasing form two-way shape memory alloy (SMA) actuator composed of SMA spring and steel spring is analyzed. Based on the force equilibrium equation, the relationship between load capacity of SMA spring and geometric parameters is established. In order to obtain the characteristics of SMA spring actuator, the output force and output displacement of SMA spring under different temperatures are analyzed by the theoretical model and the experimental method. Based on the shape memory effect of SMA, the relationship of the SMA spring actuator's output displacement with the temperature, the stress and strain, the material parameters, and the size parameters is established. The results indicate that the trend of theoretical results is basically consistent with the experimental data. The output displacement of SMA spring actuator is increased with the increasing temperature.